Review of the Spatial Distribution, Source and Extent of Heavy Metal Pollution of Soil in China: Impacts and Mitigation Approaches - Terefe Hanchiso Sodango; Xiaomei Li; Jinming Sha; Zhongcong Bao (Journal of Health and Pollution, 2018)
Background. China has undergone a rapid industrial revolution and urbanization during the past three decades. This expansion is largely responsible for the release of a large amount of heavy metals into soils and is increasingly raising concerns over the potential effects on human health and the environment. The problem is drawing increasing attention, especially after an extensive nationwide soil survey report in 2014. A number of studies have examined soil contamination by heavy metals in China. However, most of these studies have been small in scale and it is therefore challenging to get a general overview of the level of contamination across the entire country. Objectives. The present study is aimed at presenting a synthesized overview of the extent, pattern, and impact of heavy metal contamination of soils in China, including mitigation approaches. Methods. Eighty-six journal articles and other literature such as reports, internet sources, and statistical yearbooks were narratively and critically synthesized to compile a holistic summary of sources of heavy metals, the extent of pollution, spatial distribution and impact of heavy metal contamination in China. The major findings from these studies are presented, along with mitigation approaches applicable to China. Discussion. A synthesis of major findings from recent scientific journals shows that about 10.18% of farmland soils which supports 13.86% of grain production in China is affected by heavy metals. The main sources of pollution are anthropogenic activities. Even though the spatial distribution of pollution is highly variable owing to natural and human factors, provinces with intensive industrial activities such as Henan, Shandong, and Sichuan are more highly polluted than others. These regions are top grain producing areas and hence require close follow-up for development of feasible approaches to mitigating crop contamination and associated health risks emerging in parts of China. The government recently launched a program aimed at determining sound reclamation strategies. Conclusion. Mitigation of heavy metal contamination in China requires coordination of different actors and integration of all feasible reclamation approaches. Competing Interests. The authors declare no competing financial interests.